2018
DOI: 10.4236/jmp.2018.99111
|View full text |Cite
|
Sign up to set email alerts
|

Predictions of Electronic, Transport, and Structural Properties of Magnesium Sulfide (MgS) in the Rocksalt Structure

Abstract: We report results from ab-initio, self-consistent density functional theory (DFT) calculations of electronic, transport and bulk properties of rock salt magnesium sulfide (MgS). In the absence of experimental data on these properties, except for the bulk modulus, these results are predictions. Our calculations utilized the Ceperley and Alder local density approximation (LDA) potential and the linear combination of Gaussian orbitals (LCGO).The key difference between our computations and other previous ab-initio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 32 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…The PSD process was initiated using a pulsed excimer laser (GAM Laser Inc., Ex5) configured to produce UV photons at 193 nm (6.42 eV), above the band gap energy of MgS (about 3.5 eV) (Bhandari et al, 2018; Taleatu et al, 2015; Wu et al, 2014). The unfocused beam was passed through an aperture to reduce the beam diameter to about 3 mm on the target, small enough to ensure the detected signal came only from the MgS‐pressed pellet, and the sample was sufficiently thick to ensure all incident light was absorbed by the sample before interacting with the underlying Co substrate.…”
Section: Methodsmentioning
confidence: 99%
“…The PSD process was initiated using a pulsed excimer laser (GAM Laser Inc., Ex5) configured to produce UV photons at 193 nm (6.42 eV), above the band gap energy of MgS (about 3.5 eV) (Bhandari et al, 2018; Taleatu et al, 2015; Wu et al, 2014). The unfocused beam was passed through an aperture to reduce the beam diameter to about 3 mm on the target, small enough to ensure the detected signal came only from the MgS‐pressed pellet, and the sample was sufficiently thick to ensure all incident light was absorbed by the sample before interacting with the underlying Co substrate.…”
Section: Methodsmentioning
confidence: 99%
“…In the case of the Mg-doped ZnS QDs, where the average crystallite size does not exhibit significant changes, the reduction in band gap with increasing Mg dopant concentration is primarily attributed to the compositional effect. According to theoretical calculations conducted by Bhandari et al band gap of the MgS was predicted to be 3.278 eV using Density Functional Theory (DFT) calculations [ 39 ]. However, experimental results indicated that the band gap of MgS-based thin films fell within the range of 3.54 eV [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…[38] [39], as enhanced by Ekuma and Franklin (BZW-EF) [40] [41] [42] [43] [44]. We employed the local density approximation (LDA) potential of Ceperley and Alder [45] as parameterized by Vosko et al [46].…”
Section: Computational Methods and Details For Replicationmentioning
confidence: 99%